(Epi)genetics of pregnancy-associated diseases - Oudejans, Cees; Van Dijk, Marie (Frontiers in Genetics, 2013)
This review describes the current knowledge regarding genetics and epigenetics of pregnancy-associated diseases with placental origin. We discuss the effect on genetic linkage analyses when the fetal genotype determines the maternal phenotype. Secondly, the genes identified by genome-wide linkage studies to be associated with pre-eclampsia (ACVR2A, STOX1) and the HELLP-syndrome (LINC-HELLP) are discussed regarding their potential functions in the etiology of disease. Furthermore, susceptibility genes identified by candidate gene approaches (e.g., CORIN) are described. Next, we focus on the additional challenges that come when epigenetics also play a role in disease inheritance. We discuss the maternal transmission of the chromosome 10q22 pre-eclampsia linkage region containing the STOX1 gene and provide further evidence for the role of epigenetics in pre-eclampsia based on the cdkn1c mouse model of pre-eclampsia. Finally, we provide recommendations to unravel the genetics of pregnancy-associated diseases, specifically regarding clear definitions of patient groups and sufficient patient numbers, and the potential usefulness of (epi)genetic data in early non-invasive biomarker development.